2010
DOI: 10.1039/b921469k
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids in surface electrochemistry

Abstract: Ionic liquids (IL) are widely used in electrochemistry due to their excellent properties such as good ionic conductivity, wide electrochemical potential window, high viscosity, high thermal stability, wide liquid range and tunable solvent properties. In electrochemistry, the performance of an electrochemical system is dependent on the properties of the interface at the IL/electrode. This review presents the surface electrochemistry in ILs, and the interfacial structures of IL/electrode and heterogeneous electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
244
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 342 publications
(254 citation statements)
references
References 189 publications
4
244
0
1
Order By: Relevance
“…[17,[31][32][33][34] Note that the vanishingly low vapor pressure and the air and water stability of the non-chloroaluminate alkylimidazolium-based ionic liquids enable the in situ measurements to be fulfilled under more flexible environmental conditions. By employing scanning probe and spectroscopic techniques, structural information with high spatial resolution and at the molecular level has been obtained and preliminary understanding of the electrode/ionic liquid interfaces has been reached.…”
Section: Introductionmentioning
confidence: 99%
“…[17,[31][32][33][34] Note that the vanishingly low vapor pressure and the air and water stability of the non-chloroaluminate alkylimidazolium-based ionic liquids enable the in situ measurements to be fulfilled under more flexible environmental conditions. By employing scanning probe and spectroscopic techniques, structural information with high spatial resolution and at the molecular level has been obtained and preliminary understanding of the electrode/ionic liquid interfaces has been reached.…”
Section: Introductionmentioning
confidence: 99%
“…(4) Another very important area would be quantitative in situ studies of chemical reactions in ILs under electrochemical conditions; the interest in this area is driven by their huge potential in electrochemical applications. 3,20,131 Presently, one often lacks a detailed mechanistic understanding of the ongoing reactions or processes at the IL/electrode interface. In particular, the spectroscopic investigation using UHV-based surface science methods still is at its infancy due to a number of experimental challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Some ionic liquids, such as 1-butyl-1-methylpyrrolidinium bis (trifluoro methanesulfonyl) imide (C4mpyr TFSI) with LiTFSI (Howlett et al 2004(Howlett et al , 2006Liu et al 2010;Bhatt et al 2010;Lane et al 2010), have been shown to enhance uniform deposition on the lithium metal anode, thus reducing dendrite formation without additional additives. This opens up the way for the highest energy density lithium batteries of all: those employing metallic lithium as anode.…”
Section: Electrolytes Based On Ionic Liquidsmentioning
confidence: 99%